Chemical composition and in vitro digestibility of leaves of Tunisian Ajuga iva - Ammar H.; Essid S.; Brinsi J.; López S. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
This study aimed to determine chemical composition of leaves of Ajuga iva (L.) collected in winter from different Tunisian localities namely Dogga, Mograne and Nabeul. Leaves collected from Nabeul locality had high mineral contents (24.3%). High crude protein (CP) contents were recorded in leaves collected from Mograne locality (14.7%), while those collected from Dogga contained the lower levels (8.9%). Cell wall contents (NDF and ADF) varied from 29.3 to 37.0% (NDF) and from 22.2 to 30.1% (ADF). Lignification of cell wall varied between 13.5% (Nabeul) and 19.0% (Mograne). Irrespectively of their locality, methanol extracts of A. iva leaves were characterized by their high phenolic (13.6-14.0 mg gallic acid equivalent/g DM), and flavonoids (8.6-12.6 mg quercetine equivalent / g DM) contents. True in vitro dry matter digestibility (TID) varied between leaves collected from different localities but it was low (<80% DM). Results of this present study suggest that A. iva species, due to its high CP contents, would be appreciated by small ruminant grazing on natural pasture and cover part of their nutritional requirements.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)